Exploratory study on the retail and marketing environment in Singapore. - Foo, Joyce Yin Yin. (2008)
This applied research project was carried out as an exploratory study to determine whether the presence of anchor stores play a significant role in affecting customer’s patronage decisions to shopping malls.